Transformation of polyacrylamide during hydrothermal carbonization and pyrolysis - Qi, Gaoxiang (Frontiers in Chemical Engineering, 2025)
Polyacrylamide (PAM), a widely utilized flocculant in sewage treatment, typically finds its way into sewage sludge (SS) and undergoes transformation during the SS treatment process. Despite its prevalence and potential implications, the transformation of PAM during SS treatment has scarcely been documented in the literature. This study investigated the transformation of PAM during two prevalent thermal treatment processes of SS: hydrothermal carbonization (HTC) and pyrolysis. To comprehensively analyze the transformation products, LC-MS/MS was employed to examine the liquid products obtained from the HTC treatment of PAM, while TG-FTIR was utilized to analyze the pyrolysis gas. Upon subjecting PAM to HTC treatment in the temperature range of 150–240 °C, a detailed analysis of the water quality characteristics of the liquid phase derived from PAM was conducted. The analysis successfully identified a total of 81 components, consisting of 35 carbonaceous and 46 nitrogenous compounds. Notably, when the reaction temperature remained below 150 °C, the decomposition of both the side chains and the backbone of PAM was relatively mild. However, as the temperature exceeded 180 °C, the deamination process was significantly enhanced. Concurrently, the pH of the liquid phase decreased, which could be attributed to the decomposition of high molecular polybasic acids into low-molecular weight organic acids. The TG-FTIR analysis of PAM revealed that the mass loss during the pyrolysis of PAM at 30–1,000 °C could be distinctly divided into five stages. The initial mass loss stage was primarily attributed to the removal of adsorbed water and organic solvents. The second mass loss stage was hypothesized to be a result of intramolecular decomposition accompanied by the elimination of CHx and C=C groups. The subsequent third, fourth, and fifth mass loss stages were predominantly due to the release of amides and CO2. Additionally, it was observed that CO was generated through the reduction of CO2 by the carbon present in the solid residues. The conclusion of this study presents a comprehensive discussion of environmental implications based on the results of HTC and pyrolysis treatments of PAM.